Exploring the interplay between circadian rhythms and obesity: A Boolean network approach to understanding metabolic dysregulation - Meitner Cadena; George E. Barreto (PLoS ONE, 2025)
This study investigates the interaction between circadian rhythms and lipid metabolism disruptions in the context of obesity. Obesity is known to interfere with daily rhythmicity, a crucial process for maintaining brain homeostasis. To better understand this relationship, we analyzed transcriptional data from mice fed with normal or high-fat diet, focusing on the mechanisms linking genes involved with those regulating circadian rhythms. We performed biological enrichment analysis and Boolean network modeling to identify direct interactions between these genes. The resulting mathematical model provided a comprehensive system of gene interactions, primarily highlighting lipid metabolism. Our findings revealed key insights into the effects of obesity on circadian rhythm genes, particularly the under-expression of core genes such as Bmal1 and Clock. Crucially, we identified a reciprocal interaction between obesity and circadian genes, where disruptions on one exacerbated the dysfunction in the other. This mechanism suggests that the disruption of circadian rhythms plays a pivotal role in worsening the metabolic disturbances associated with obesity, providing new perspectives for targeting circadian pathways in obesity-related metabolic disorders.